KEANEKARAGAMAN BURUNG PEMAKAN BUAH DI HUTAN KAMPUS UNIVERSITAS BANGKA BELITUNG - Aeng Saputra; Nur Annis Hidayati; Ani Mardiastuti (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2020)
Avian frugivores or Fruit-eating birds have an important role in spreading plant seeds so that they can maintain stability and continuation of nature. The forest of the bangka belitung university has a vast forest area and quite high diversity. Data related to avian frugivores at Bangka Belitung University has never been published. This study aims to determine the diversity and distribution of fruit-eating birds in the Bangka Belitung University campus forest. This research was conducted at ten observation points using the Point count method. The point count method is the observation method at a predetermined location where the researcher stands at a research point with a fixed period of time. Based on the results of the research that has been conducted, there were 182 individuals belonging to 20 species and 9 families found at 10 observation points. There are three families belonging to the group of fruit-eating birds namely Columbidae, Dicaeidae and Pycnonotidae with a percentage of 77%. The most abundant fruit-eating bird species is Pycnonotus aurigaster. The highest diversity level was found at the 4th observation point, while based on the number of individuals fruit-eating birds were found at the 10th observation point. This is because the two locations have structures and compositions that can support the life of avian frugivores